Development of a Simple and Fast Electrochemical Method for Screening and Stoichiometric Determination of Dimenhydrinate. Issue 9 (19th August 2014) - Machado Freitas, Jhonys; da Costa Oliveira, Thiago; Silva, Polyana Luiza; Tofanello Gimenes, Denise; Abarza Munoz, Rodrigo Alejandro; Richter, Eduardo Mathias
Abstract Dimenhydrinate (DIM) is a salt composed by the combination of two active pharmaceutical ingredients: diphenhydramine (DIP) and 8‐chlorotheophylline (CTP). In this work, the use of batch injection analysis with multiple pulse amperometric detection (BIA‐MPA) was proposed for the first time for fast stoichiometric determination of DIM. DIP (cation) and CTP (anion) were determined simultaneously in pharmaceutical samples with a simple and fast injection procedure (70 injections h−1). Additional strategies were also proposed for rapid screening of samples containing the DIM salt. By a simple injection of a sample into the BIA system (without using of calibration curve), reliable information about stoichiometry of the DIM salt (1 : 1; DIP:CTP) and presence or absence of interfering species (electroactive) can be achieved.